Comparison of CERES-MODIS cloud microphysical properties with surface observations over Loess Plateau. (March 2015) - Yan, Hongru; Huang, Jianping; Minnis, Patrick; Yi, Yuhong; Sun-Mack, Sunny; Wang, Tianhe; Nakajima, Takashi Y.
Abstract: To enhance the utility of satellite-derived cloud properties for studying the role of clouds in climate change and the hydrological cycle in semi-arid areas, it is necessary to know their uncertainties. This paper estimates the uncertainties of several cloud properties by comparing those derived over the China Loess Plateau from the MODerate-resolution Imaging Spectroradiometer (MODIS) on Terra and Aqua by the Clouds and Earth׳s Radiant Energy System (CERES) with surface observations at the Semi-Arid Climate and Environment Observatory of Lanzhou University (SACOL). The comparisons use data from January 2008 to June 2010 limited to single layer and overcast stratus conditions during daytime. Cloud optical depths ( τ ) and liquid water paths (LWP) from both Terra and Aqua generally track the variation of the surface counterparts with modest correlation, while cloud effective radius ( r e ) is only weakly correlated with the surface retrievals. The mean differences between Terra and the SACOL retrievals are −4.7±12.9, 2.1±3.2 μm and 30.2±85.3 g m −2 for τ, r e and LWP, respectively. The corresponding differences for Aqua are 2.1±8.4, 1.2±2.9 μm and 47.4±79.6 g m −2, respectively. Possible causes for biases of satellite retrievals are discussed through statistical analysis and case studies. Generally, the CERES-MODIS cloud properties have a bit larger biases over the Loess Plateau than those in previous studies over other locations. Highlights: We assess the accuracy of CERES-MODIS cloud properties in remote region of China. The methodology includes both statistical analysis and specific case study. We thoroughly discuss probable error sources for satellite-surface retrievals difference. We discuss differences and consistency between this paper and other studies.